Databank of Eleven Spanish Novels 1951–1971 - Språkbanken Text (University of Gothenburg, 2024)
This corpus consists of 11 novels from Spanish authors, written between 1952
and 1971. Each novel was written by a different author and the text included
is that of the first edition in Spanish. The purpose of the corpus is to
create electronic texts of the period to facilitate the study of the Spanish
language, and also to create utilities for linguistic and literary studies.
This corpus is part of the collection SOL - Spanish Online.

Korpusen består av 11 romaner av spanska författare, skrivna mellan 1951
och 1971. Alla romaner är skriven av olika författare. Texterna som ingår
i korpusen hör till den första utgåvan av romanerna på spanska. Syftet
med korpusen var att skapa digitala texter av denna tidsperiod för att
underlätta studier av det spanska språket, och att skapa hjälpmedel för
lingvistiska och litterära studier. Texterna är på spanska. Korpusen
ingår i samlingen SOL - Spanska Online.
Banco de Datos de Once Novelas Españolas 1951–1971
Keywords: Language Technology (Computational Linguistics); novel; Spanish; Spain; 20th century; 1950s; 1960s; 1970s; literature; corpus; Natural Language Processing; Språkbehandling och datorlingvistik